2013
DOI: 10.1097/sla.0000000000000157
|View full text |Cite
|
Sign up to set email alerts
|

Reintervention after EVAR and Open Surgical Repair of AAA

Abstract: Reintervention was more common with EVAR and occurred later. Early reintervention after OSR is associated with significant mortality. If early reintervention in OSR patients can be avoided, there is no early survival advantage to EVAR. Current endografts require fewer reinterventions than earlier devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…9 Prior studies found a declining rate of late reinterventions following EVAR with newer generation endografts. 7, 21, 22 While we studied early interventions, we also noticed a very low rate of vascular-related reinterventions among the EVAR patients (< 2%), which may reflect better outcomes with these more modern endografts between 2012 and 2014. Indeed, fully one in five of the reinterventions from the EVAR-1 trial (corresponding to 2% of all EVARs performed), underwent conversion to open repair within the first 30-days, while only three patients (< 0.1%) in our modern series underwent conversion to open repair.…”
Section: Discussionmentioning
confidence: 86%
“…9 Prior studies found a declining rate of late reinterventions following EVAR with newer generation endografts. 7, 21, 22 While we studied early interventions, we also noticed a very low rate of vascular-related reinterventions among the EVAR patients (< 2%), which may reflect better outcomes with these more modern endografts between 2012 and 2014. Indeed, fully one in five of the reinterventions from the EVAR-1 trial (corresponding to 2% of all EVARs performed), underwent conversion to open repair within the first 30-days, while only three patients (< 0.1%) in our modern series underwent conversion to open repair.…”
Section: Discussionmentioning
confidence: 86%
“…Traditionally, patients having EVAR have been shown to have a higher rate of reintervention than those undergoing OAR. The analysis of reinterventions in the present study is limited because the follow‐up for reintervention was restricted to 1 year; it is quite possible that many reinterventions occur during longer‐term follow‐up. Although the rates of reintervention are similar, it is not possible to determine the scale of reintervention for either technique.…”
Section: Discussionmentioning
confidence: 92%
“…As such, regular life‐long repeat imaging will be necessary to allow detection and correction of these complications. Reintervention rate was also found to be higher in patient with EVAR (9%) than in those treated with open surgical repair (1.7%), with endoleaks responsible for 66% of EVAR reinterventions …”
Section: Discussionmentioning
confidence: 90%